2007
DOI: 10.1186/1477-7525-5-1
|View full text |Cite
|
Sign up to set email alerts
|

How young can children reliably and validly self-report their health-related quality of life?: An analysis of 8,591 children across age subgroups with the PedsQL™ 4.0 Generic Core Scales

Abstract: Background: The last decade has evidenced a dramatic increase in the development and utilization of pediatric health-related quality of life (HRQOL) measures in an effort to improve pediatric patient health and well-being and determine the value of healthcare services. The emerging paradigm shift toward patient-reported outcomes (PROs) in clinical trials has provided the opportunity to further emphasize the value and essential need for pediatric patient self-reported outcomes measurement. Data from the PedsQL™… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
570
5
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 759 publications
(616 citation statements)
references
References 49 publications
(39 reference statements)
30
570
5
11
Order By: Relevance
“…However, the definition of these age groups is not straightforward. Although studies generally endorse the idea that any school-aged child can self-report his or her health [101] and despite evidence of reliable QL self-reports from children five years and older [102], in the context of the present review, it is suggested that school-aged children and adolescents with mental disorders can be clustered within the age groups of 8-12 years and 13-18 years old, respectively, as a harmonized guideline for research. This guideline is in agreement with the methodological options of previous world-renowned pediatric QL projects, such as KIDSCREEN [103], PedsQL [94] and DISABKIDS [97].…”
Section: Discussionmentioning
confidence: 99%
“…However, the definition of these age groups is not straightforward. Although studies generally endorse the idea that any school-aged child can self-report his or her health [101] and despite evidence of reliable QL self-reports from children five years and older [102], in the context of the present review, it is suggested that school-aged children and adolescents with mental disorders can be clustered within the age groups of 8-12 years and 13-18 years old, respectively, as a harmonized guideline for research. This guideline is in agreement with the methodological options of previous world-renowned pediatric QL projects, such as KIDSCREEN [103], PedsQL [94] and DISABKIDS [97].…”
Section: Discussionmentioning
confidence: 99%
“…Children are found to be able to reliably and validly self-report their QoL by the age of 5 years if the instrument that is applied is age-appropriate (Varni, Limbers, & Burwinkle, 2007). Recent recommendations ) underline the importance of using developmentally appropriate language and techniques to ensure that outcomes have content validity.…”
Section: Can We Rely On Children's Reports Of Their Qol?mentioning
confidence: 99%
“…So, parents of preschool children become proxy assessors of their children's health. Moderate to good agreement was observed between parent proxy and child reporting in previous studies which had evaluated parent and child agreement on HRQOL assessment [4].…”
Section: Introductionmentioning
confidence: 63%